Evaluate the Financial Performance of Private banks registered in the Iraq Stock Exchange (An Analytical Study) - Ahmed Abbas Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The research aims to evaluate the financial performance of a sample of banks registered in the (Iraq Stock Exchange) through the use of some financial evaluation indicators, which included indicators of liquidity and profitability and the presentation of data for the period 2015-2018, and the research sample included three banks:(Ashur International Bank, Commercial Bank of Iraqi, and Gulf Commercial Bank), as well as identifying the role of other financial indicators represented by the capital adequacy ratios and activity ratios in the evaluation. The research reached a set of recommendations, the most important of which is the need for banks to rely on the process of evaluating banking financial performance in order to reach each of their strengths and weaknesses in order to improve their future.